Structural Brain Damage and Upper Limb Kinematics in Children with Unilateral Cerebral Palsy - Mailleux, Lisa; Simon-Martinez, Cristina; Klingels, Katrijn; Jaspers, Ellen; Desloovere, Kaat; Demaerel, Philippe; Fiori, Simona; Guzzetta, Andrea; Ortibus, Els; Feys, Hilde (Frontiers in Human Neuroscience, 2017)
Background In children with unilateral cerebral palsy (uCP) virtually nothing is known on the relation between structural brain damage and upper limb (UL) kinematics quantified with three-dimensional movement analysis (3DMA). This explorative study aimed to (1) investigate differences in UL kinematics between children with different lesion timings, i.e. periventricular white matter (PWM) versus cortical and deep gray matter (CDGM) lesions and (2) to explore the relation between UL kinematics and lesion location and extent within each lesion timing group. Methods Forty-eight children (age 10.4y ± 2.7y; 29 boys; 21 right-sided; 33 PWM; 15 CDGM) underwent an UL 3DMA during a reach-to-grasp task. Spatiotemporal parameters (movement duration, (timing of) maximum velocity, trajectory straightness), the Arm Profile Score (APS) and Arm Variable Scores (AVS) were extracted. The APS and AVS refer to the total amount of movement pathology and movement deviations of the wrist, elbow, shoulder, scapula and trunk respectively. Brain lesion location and extent were scored based on FLAIR-images using a semi-quantitative MRI-scale. Results Children with CDGM lesions showed more aberrant spatiotemporal parameters (p<0.03) and more movement pathology (APS, p=0.003) compared to the PWM group, mostly characterized by increased wrist flexion (p=0.01). In the CDGM group, moderate to high correlations were found between lesion location and extent and duration, timing of maximum velocity and trajectory straightness (r=0.53-0.90). Lesion location and extent were further moderately correlated with distal UL movement pathology (wrist flexion/extension, elbow pronation/supination, elbow flexion/extension; r=0.50-0.65) and with the APS (r=0.51-0.63). In the PWM group, only a few and low correlations were observed, mostly between damage to the PLIC and higher AVS of elbow flexion/extension, shoulder elevation and trunk rotation (r=0.35-0.42). Regression analysis revealed damage to the temporal lobe with lesion timing as interactor (27%, p=0.002) and the posterior limb of the internal capsule (PLIC) (7%, p=0.04) as the strongest predictors, explaining 34% of the variance in APS. Conclusion UL kinematic deviations are more influenced by lesion location and extent in children with later (CDGM) versus earlier lesions (PWM), except for proximal movement pathology. Damage to the PLIC is a significant predictor for UL movement pathology irrespective of lesion timing.